Economic Aspects of Adaptation to Climate Change Integrated Assessment Modelling of Adaptation Costs and Benefits - de Bruin, Kelly (OECD Publishing, 2009)
The present report seeks to inform critical questions with regard to policy mixes of investments in adaptation and mitigation, and how they might vary over time. This is facilitated here by examining adaptation within global Integrated Assessment Modelling frameworks. None of the existing Integrated Assessment Models (IAMs) captures adaptation satisfactorily. Many models do not specify the damages from climate change, and those that do mostly assume implicitly that adaptation is set at an "optimal" level that minimizes the sum total of the costs of adaptation and the residual climate damages that might occur. This report develops and applies a framework for the explicit incorporation of adaptation in Integrated Assessment Models (IAMs). It provides a consistent framework to investigate "optimal" balances between investments in mitigating climate change, investments in adapting to climate change and accepting (future) climate change damages.
Keywords: Environment